2017
DOI: 10.1515/cclm-2016-0700
|View full text |Cite
|
Sign up to set email alerts
|

The use of liquid chromatography-tandem mass spectrometry for therapeutic drug monitoring of antibiotics in cancer patients

Abstract: Cancer remains a leading cause of mortality and morbidity worldwide. In addition to organ failure, the most frequent reasons for admission of cancer patients to intensive care units (ICU) are: infections and sepsis. As critically ill, the complexity of the health situation of cancer patients renders the standard antimicrobial regimen more complex and even inadequate which results in increased mortality rates. This is due to pathophysiological changes in the volume of distribution, increased clearance, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 98 publications
(173 reference statements)
0
11
0
Order By: Relevance
“…Therefore, the optimal diagnostic choice currently seems to be chromatography combined with mass spectrometry (LC-MS), which is mostly based on locally developed standards [ 16 ]. Although the application of LC-MS requires a sophisticated infrastructure including trained personnel and extensive apparatuses, the number of hospitals incorporating LC-MS in routine analysis is increasing [ 18 ]. This might be explained due to decreased costs of LC-MS equipment compared to earlier eras, but also as a consequence of improved sensitivity and speed [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the optimal diagnostic choice currently seems to be chromatography combined with mass spectrometry (LC-MS), which is mostly based on locally developed standards [ 16 ]. Although the application of LC-MS requires a sophisticated infrastructure including trained personnel and extensive apparatuses, the number of hospitals incorporating LC-MS in routine analysis is increasing [ 18 ]. This might be explained due to decreased costs of LC-MS equipment compared to earlier eras, but also as a consequence of improved sensitivity and speed [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the application of LC-MS requires a sophisticated infrastructure including trained personnel and extensive apparatuses, the number of hospitals incorporating LC-MS in routine analysis is increasing [ 18 ]. This might be explained due to decreased costs of LC-MS equipment compared to earlier eras, but also as a consequence of improved sensitivity and speed [ 18 , 19 ]. The application of this technique enables fast turnaround times, which in turn benefits patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, DDI can play a significant role in the increase in mortality and morbidity of cancer patients [4]. This is not surprising as the complicated health situation of cancer patients necessitates in many instances the concomitant administration of a wide range of medications such as immunosuppressant and anti-infective agents along with antineoplastic agents [5]. A study by Poulikakos et al, showed a mortality rate of 100% of cancer patients after an influenza infection even though a proper treatment was received [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers in this issue of Clinical Chemistry and Laboratory Medicine emphasize the wide range of applications of MS based methods [23][24][25][26][27][28][29][30]. The review by El-Najjar et al [23] highlights the crucial role of TDM of antibiotics in cancer patients: immunoassays are not available for all the classes of these drugs due to the difficulty in β-lactams ring reactivity or degradation.…”
mentioning
confidence: 99%
“…The review by El-Najjar et al [23] highlights the crucial role of TDM of antibiotics in cancer patients: immunoassays are not available for all the classes of these drugs due to the difficulty in β-lactams ring reactivity or degradation. Therefore, LC-MS/MS methods have become the method of choice.…”
mentioning
confidence: 99%